Nonsuicidal self-injury as the gateway and consequence of suicidal ideation among adolescents: a cross-lagged regression analysis - Xu, Zhansheng; Li, Nianqin; Kong, Yaxin; Lin, Lin; Liu, Yu; Zhang, Huan; He, Yunfeng; Zhao, Song (Frontiers in Psychiatry, 2024)
Background: There is a consensus that both nonsuicidal self-injury (NSSI) and suicidal ideation as risk factors for suicidal behavior have a strong connection.However, a lack of longitudinal information has limited the clarification of the concrete relationship between them. Aims: This study aimed to examine the specific mechanism between NSSI and suicidal ideation over time, during adolescence.Method: A longitudinal study was conducted with 193 Chinese adolescents. NSSI and suicidal ideations were examined over the course of a 1year followed-up, and three waves of data were collected. Results: The NSSI at time T1 significantly positively predicted suicidal ideation at time T2; Suicidal ideation at time T2 also significantly positively predicted NSSI at time T3. Limitations: Given that the small number of participants with suicidal ideation and NSSI, the findings of the study should be interpreted with caution and a lager sample is needed in the future. Conclusion: It was suggested that NSSI may occur before suicidal ideation, which in turn would strengthen NSSI, so interventions should be carried out from two aspects (behaviors and thoughts) to improve adolescents' mental health.